Ukrainekrieg: Was sagen mehr als 8 Mio. Tweets? - Moritz Grebe; Sinem Kandemir; Peter Tillmann (Wirtschaftsdienst, 2023)
– We collect more than eight million German-language tweets on the war in Ukraine and use a machine learning approach toconstruct a daily index of uncertainty about the war. In an empirical model, we show that fluctuations in uncertainty have strong effectson financial markets and real economic activity in Germany.
Keywords: D8; E3; G1; 330